Workshop Berkreasi Dengan Canva Untuk Para Pengurus Bina Keluarga Lansia Periuk Kota Tangerang - tri santoso; Adelia Alvi Yana; Ardian Dwi Praba; Sulistianto SW (CV. Multi Kreasi Media, 2023)
The conditions of the Covid-19 Pandemic that we used to experience are now starting to gradually improve. This can be seen from the many community activities that are starting to be active again, various sectors are coming back to life. The wheels of the economy began to run again. This condition also affects the activities of the Elderly Family Development (BKL) in Periuk, Tangerang City. Many activities were halted as a result of the effects of the Covid-19 Pandemic. But now there are many activities that want to be held again. With many of these activities, a lot of reporting, documentation and posters are also needed for these activities. On the basis of these problems, this community service was carried out to serve as a supporting medium for activities at BKL Periuk, Tangerang City. Because at this BKL there are a lot of activities that are active again, it usually requires making advertisements in the form of brochures and posters that are used as information media for the activities to be held. It should be noted that the management at this BLK are not proficient enough in making graphic designs to support the activities that will be held and disseminated to the general public either through the assembly's social media or distributed manually. For this reason, in order to provide training and increase their knowledge and insight, this community service was held to increase the skills of the administrators in making advertisements, whether in the form of brochures or poster.